The IgG glycome of SARS-CoV-2 infected individuals reflects disease course and severity - Siekman, Sterre L.; Pongracz, Tamas; Wang, Wenjun; Nouta, Jan; Kremsner, Peter G.; da Silva-Neto, Pedro Vieira; Esen, Meral; Kreidenweiss, Andrea; Held, Jana; Trapé, Átila Alexandre; Fendel, Rolf; de Miranda Santos, Isabel Kinney Ferreira; et al. (Frontiers in Immunology, 2022)
Immunoglobulin G (IgG) antibodies play an important role in the immune response against viruses such as SARS-CoV-2. As the effector functions of IgG are modulated by N-glycosylation of the Fc region, the structure and possible function of the IgG N-glycome has been under investigation in relation to divergent COVID-19 disease courses. Through LC-MS analysis we studied both total IgG1 and spike protein-specific IgG1 Fc glycosylation of 129 German and 163 Brazilian COVID-19 patients representing diverse patient populations. We found that hospitalized COVID-19 patients displayed decreased levels of total IgG1 bisection and galactosylation and lowered anti-S IgG1 fucosylation and bisection as compared to mild outpatients. Anti-S IgG1 glycosylation was dynamic over the disease course and both anti-S and total IgG1 glycosylation were correlated to inflammatory markers. Further research is needed to dissect the possible role of altered IgG glycosylation profiles in (dys)regulating the immune response in COVID-19.